On some technology of project modeling of stochastic manufacturing technological processes - Maksimey, I.V.; Levchuk, V.D.; Smorodin, V.S.; Maslovich, S.F.; Popova, E.O.; Potashenko, A.M.; Starchenko, V.V.; Tereschenko, G.A. (Інститут програмних систем НАН України, 2015)
Principles of modification of program—technological simulation tools of stochastic discrete technological processes are described for the following problem fields: investigation of computing processes; simulation of assemble and disassemble jobs; models of stochastic net scheduling, post offices, discrete manufacturing processes with unreliable equipment.